SAT0469 Integrated efficacy analysis of tofacitinib, an oral janus kinase inhibitor, in patients with active psoriatic arthritis. (15th June 2017) - Nash, P; Coates, LC; Fleischmann, R; Papp, KA; Gomez-Reino, JJ; Kanik, KS; Wang, C; Wu, J; Hendrikx, T; Ports, WC
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor under investigation for treatment of psoriatic arthritis (PsA). Objectives: To determine efficacy based on pooled data from 2 pivotal Phase 3 studies of tofacitinib in patients (pts) with active PsA. Methods: Data were pooled from 2 placebo (PBO)-controlled, double-blind, multicentre, global Phase 3 studies (OPAL Broaden [N=422; 12 months; NCT01877668 ]; OPAL Beyond [N=394; 6 months; NCT01882439 ]). Pts had active PsA and either inadequate response (IR) to ≥1 conventional synthetic disease-modifying antirheumatic drug (csDMARD) and were tumour necrosis factor inhibitor (TNFi)-naïve (OPAL Broaden), or had IR to ≥1 TNFi (OPAL Beyond). Pts were randomised to tofacitinib 5 mg twice daily (BID), 10 mg BID, adalimumab 40 mg subcutaneous injection once every 2 weeks (OPAL Broaden only) or PBO, in addition to a single, stable background csDMARD. PBO pts advanced to tofacitinib 5 mg or 10 mg BID at Month (M)3. Endpoints included ACR20/50/70 response rates (≥20%, ≥50% and ≥70% improvement), change from baseline (Δ) in HAQ-DI (Health Assessment Questionnaire-Disability Index), HAQ-DI response (decrease from baseline [BL] of ≥0.35), PASI75 (≥75% improvement from BL in Psoriasis Area and Severity Index), ΔLEI (Leeds Enthesitis Index) and enthesitis absence, ΔDSS (Dactylitis Severity Score) and dactylitis absence and ΔDLQI (Dermatology Life Quality Index). Pooled data only included tofacitinib 5 mg and 10 mg BID (to M6) and PBO (to M3). Significance was declared for p≤0.05 without correction for multiplicity. Results: For pooled data, pts were predominantly white (94.2%) and female (55.4%) with ≥5 peripheral swollen or tender joints (98.0%), enthesitis (LEI>0; 67.5%), dactylitis (DSS>0; 52.5%), psoriatic body surface area ≥3% (67.7%) and CRP levels above the upper limit of normal (>2.87 mg/L; 62.5%) at BL. Mean age was 49.1 years and PsA duration was 8.0 years. Significant improvements vs PBO at M3 were observed for peripheral arthritis and physical function endpoints for tofacitinib 5 mg and 10 mg BID: ACR20, ACR50, ACR70, ΔHAQ-DI (least squares mean [LSM]), and HAQ-DI response (Table 1 ). Significant improvements in psoriasis, enthesitis and dactylitis endpoints vs PBO were also observed for tofacitinib 5 mg and 10 mg BID at M3: PASI75, ΔLEI, enthesitis absence based on LEI, ΔDSS (LSM), dactylitis absence based on DSS and ΔDLQI (Table 1 ). Efficacy was maintained or further improved at M6. Conclusions: In a pooled analysis of csDMARD-IR/TNFi-naïve and TNFi-IR pts, tofacitinib 5 mg and 10 mg BID were superior to PBO at M3 across four PsA disease domains: peripheral arthritis, psoriasis, enthesitis and dactylitis. Acknowledgements: This study was sponsored by Pfizer Inc. Editorial support was provided by K Haines of CMC and was funded by Pfizer Inc. Disclosure of Interest: P. Nash Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Novartis, Pfizer Inc, Roche, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Merck, Novartis, Pfizer Inc, Sanofi, Roche, UCB, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Novartis, Pfizer Inc, Roche, UCB, L. Coates Speakers bureau: Pfizer Inc, R. Fleischmann Grant/research support from: Abbott, Amgen, Astellas, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Genentech, Eli Lilly, Janssen, Novartis, Pfizer Inc, Regeneron, Sanofi Aventis, Roche, UCB, Consultant for: Abbott, Akros, Amgen, Bristol-Myers Squibb, Celgene, Genentech, Eli Lilly, Janssen, Novartis, Pfizer Inc, Sanofi Aventis, UCB, K. Papp Grant/research support from: Abbott, Amgen, Anacor, Astellas, Celgene, Celtic, Dow Pharma, Eli Lilly, Galderma, Janssen, Janssen Biotech (Centocor), Merck, Novartis, Pfizer Inc, Consultant for: 3M, Abbott, Akros, Alza, Amgen, Astellas, Baxter, Boehringer Ingelheim, Celgene, Cipher, Eli Lilly, Forward Pharma, Funxional Therapeutics, Galderma, Genentech, Isotechnika, Janssen, Janssen Biotech (Centocor), J&J, Kirin, Kyowa, Meiji Seika Pharma, Merck, Mitsubishi Pharma, Mylan, Novartis, Pfizer Inc, Regeneron, Sanofi Aventis, Serono, Stiefel, Takeda, UCB, Speakers bureau: 3M, Abbott, Amgen, Astellas, Boehringer Ingelheim, Celgene, Eli Lilly, Galderma, Janssen, Merck, Novartis, Pfizer Inc, J. Gomez-Reino Grant/research support from: AbbVie, Novartis, Pfizer Inc, Roche, UCB, Consultant for: Pfizer Inc, Speakers bureau: AbbVie, Bristol-Myers Squibb, Janssen, MSD, Pfizer Inc, Roche, UCB, K. Kanik Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang: None declared, J. Wu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Hendrikx Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, W. Ports Shareholder of: Pfizer Inc, Employee of: Pfizer Inc